Digital Transformation And E-Commerce Adoption: A Comparative Study - Jabbi, Ebrima (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
Global business landscapes were fundamentally changed by the advent of digital transformation, particularly in the e-commerce sector. In two culturally and economically distinct nations (Indonesia and The Gambia), this cross-country comparative study examines the implementation of digital transformation and its impact on the adoption of e-commerce. The foundation of this study is the examination of government programs, technological infrastructure, consumer behavior, and business adaptability, all of which clearly illustrate the factors that contributed to the development of the major e-commerce companies in these two countries. However, Indonesia has already benefited from large investments in fintech, mobile technology, and digital infrastructure, all of which have fueled its e-commerce environment as a developing Southeast Asian economy. The Gambia, a West African country with limited internet coverage and low digital literacy, is improving with Youth-Driven Digital Engagement and Mobile Banking innovations. This study analyzes digital readiness, socio-economic barriers, consumer behavior trends, public-private partnerships, regional trade policies, and ICT education, providing actionable insights for promoting inclusive digital economies.